Peningkatan Kesadaran Lingkungan Melalui Edukasi Bahaya Sampah Plastik dan Pelatihan Daur Ulang Kreatif bagi Siswa SDN 1 Seumet, Montasik, Aceh Besar - Handayani, Lia; Maulidya, Rulita; Asri, Nur; Maya, Nurul (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
Plastic waste poses a serious global challenge with significant environmental and health impacts, largely driven by low public awareness of waste management and the excessive use of plastics. Elementary school years, often referred to as the golden age, represent a crucial stage in shaping character and behavior, making early environmental education a strategic foundation for long-term ecological awareness. This Community Service Program (PKM) was designed to enhance environmental consciousness by providing education on the dangers of plastic waste and hands-on creative recycling training for students at SDN 1 Seumet, Montasik District, Aceh Besar. Conducted on August 14, 2025, the program engaged lecturers, students from Community Service Group 33 of Universitas Abulyatama, and school teachers. Activities included educational sessions, video presentations, interactive discussions, and practical workshops on recycling plastic into simple artworks. Evaluation through observation, reflective discussions, and questionnaires revealed improved student understanding of plastic pollution, adoption of 3R principles (Reduce, Reuse, Recycle), and the ability to create value-added products from waste materials. Furthermore, students demonstrated growing awareness of reducing single-use plastics and embracing eco-friendly alternatives. Overall, the program effectively fostered environmental responsibility during the golden age of development, with the potential to generate lasting positive impacts on both the school and the surrounding community.